Radiation of Sound Waves by a Semi-Infinite Duct with Outer Lining and Perforated End - TIRYAKIOGLU, Burhan (Archives of Acoustics, 2020)
Radiation of sound waves from a semi-infinite cylindrical duct with perforated end whose outer wall is coated with acoustically absorbent material is investigated by using the Wiener-Hopf technique in conjunction with the mode matching technique. A semi-infinite duct with a perforated screen can be used as a model for many engineering applications, such as noise reduction in exhausts of automobile engines, in modern aircraft jet, and turbofan engines. In particular, we aim to find the effects of outer lining and perforated end to sound pressure level for the underlying problem by using the standard Wiener-Hopf and mode matching techniques. We also present some numerical illustrations by determining the sound pressure level for different parameters such as soft and rigid outer surface, with and without perforated end, etc. Such investigations are useful in the reduction of noise effects generated through variety of sources.